(PHENOTHIAZINYL)VINYL-INDOLIUM CATIONIC DYES - BRÉM, Balázs; COLANGE, Quentin; GÁL, Emese; PORUMB, Dan Ioan; CRISTEA, Castelia; GĂINĂ, Luiza; LOVÁSZ, Tamás; SILAGHI-DUMITRESCU, Luminiţa (Studia Universitatis Babeș-Bolyai Chemia, 2018)
New 2-(2-(10H-phenothiazin-3yl)vinyl)-3H-indolium cationic dyes were successfully prepared by Knoevenagel condensation of 1,2,3,3-tetramethyl-3H-indolium iodide with 10-methyl-10H-phenothiazine-3-carbaldehyde and 10H-phenothiazine-3-carbaldehyde respectively. Their optical properties were emphasized by UV-Vis absorption spectroscopy. The position of their characteristic intramolecular charge transfer absorption maxima is situated in the visible range (550-630 nm), exhibiting solvatochromism induced by solvent polarity. Experimental evidences of linear optical properties were completed by a theoretical DFT computational study.